2006
DOI: 10.1001/jama.296.21.2590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Colorectal Cancer Staging With Whole-Body PET/CT Colonography

Abstract: In this preliminary study, PET/CT colonography is at least equivalent to CT + PET for tumor staging in patients with colorectal cancer. Thus, PET/CT colonography in conjunction with optical colonoscopy may be a suitable concept of tumor staging for patients with colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(60 citation statements)
references
References 32 publications
1
57
1
1
Order By: Relevance
“…The reason for this is predominantly related to specificity issues with the structural abnormalities found by this modality. Because combined 18 F-FDG PET/CT has already shown its superiority over PET or CT alone in staging and restaging of patients with colorectal cancer, patients with inconclusive ceCT findings now are being frequently referred for further evaluation with 18 F-FDG PET/CT (11,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this is predominantly related to specificity issues with the structural abnormalities found by this modality. Because combined 18 F-FDG PET/CT has already shown its superiority over PET or CT alone in staging and restaging of patients with colorectal cancer, patients with inconclusive ceCT findings now are being frequently referred for further evaluation with 18 F-FDG PET/CT (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…A size-related cutoff of 1.0-cm short-axis diameter has been used to define malignant lymph nodes on ceCT only. Recent publications have shown that in different areas malignant lymph node sizes can vary between medical conditions and tumor entities (17,22). However, a general 1.0-cm threshold for lymph node assessment is still widely accepted, and further research must be done with regard to lymph node sizes in different body compartments under different medical conditions.…”
Section: Figurementioning
confidence: 99%
“…In PET/CT scans involving 18 F-FDG a possibility of accurate assessment of the T stage was documented in many diagnoses, e.g. in head and neck tumors, non-small-cell carcinoma of the lungs and large intestine cancer [26][27][28][29]. The evaluation of local tumor invasion is based primarily on morphological data, that is why the MR component in PET/MR scans may turn out to be better than CT in PET/CT scans, especially in those tumors, in which high soft tissue contrast in MR images would enable higher image accuracy, as for example, in breast, prostate, head and neck, liver cancer, muscle and bone system or brain tumors.…”
Section: Application Of Pet/mr Scans In Oncologymentioning
confidence: 99%
“…T staging FDG PET/CT has been shown to be capable of accurately determining T stage in a few indications, such as head and neck tumors, non-small lung cancer and colorectal cancer [25][26][27][28]. However, since the evaluation of local tumor extent relies mainly on morphological data because of high spatial resolution, and the functional component of hybrid imaging does not add information on T stage, PET/MRI could prove to be superior to PET/CT in those indications in which MRI has been found to be more accurate than CT.…”
Section: Whole-body Fdg Pet/mrimentioning
confidence: 99%